Enhancement of antibody synthesis in rats by feeding cis-9,trans-11 conjugated linoleic acid during early life (2011)
Previous studies have demonstrated that the intake of a 1% conjugated linoleic acid (CLA) diet in an 80:20 mixture of cis-9,trans-11 and trans-10,cis-12 exerts age-specific effects on the immune system: immunoglobulin enhancement and proliferative down-modulation in neonatal and adult rats, respectively. The present study evaluates the influence of the same diet on antibody synthesis of early infant Wistar rats during suckling and/or after weaning. Dietary supplementation was performed during suckling and early infancy (4 weeks), only during suckling (3 weeks), or only in early infancy (1 week). CLA content in plasma and serum immunoglobulin (Ig) G, IgM and IgA concentration were determined. Proliferation, cytokines and Ig production were evaluated on isolated splenocytes. Cis-9,trans-11- and trans-10,cis-12-CLA isomers were detected in the plasma of all CLA-supplemented animals, and the highest content was quantified in those rats supplemented over the longest period. These rats also exhibited higher concentrations of serum IgG, IgM and IgA. Moreover, splenocytes from CLA-supplemented rats showed the highest IgM and IgG synthesis and interleukin (IL)-6 production, whereas their proliferative ability was lower. In summary, in infant rats, we observed both the enhance antibody synthesis previously reported in neonates, and the reduced lymphoproliferation previously reported in adults.